Inside Back Cover: Ligand‐Induced Evolution of Intrinsic Fluorescence and Catalytic Activity from Cobalt Ferrite Nanoparticles (ChemPhysChem 8/2015). Issue 8 (8th June 2015) - Pal, Monalisa; Kundu, Anirban; Rakshit, Rupali; Mandal, Kalyan
Abstract : Through the facile surface modification of CoFe2 O4 nanoparticles with tartrate ligands, intrinsic multicolor fluorescence covering the whole visible region was achieved, as described by M. Pal et al. onp. 1627. These nanoparticles also showed excellent photocatalytic activity.